2012
DOI: 10.1371/journal.pone.0047105
|View full text |Cite
|
Sign up to set email alerts
|

N-Chlorotaurine, a Long-Lived Oxidant Produced by Human Leukocytes, Inactivates Shiga Toxin of Enterohemorrhagic Escherichia coli

Abstract: N-chlorotaurine (NCT), the main representative of long-lived oxidants produced by granulocytes and monocytes, is known to exert broad-spectrum microbicidal activity. Here we show that NCT directly inactivates Shiga toxin 2 (Stx2), used as a model toxin secreted by enterohemorrhagic Escherichia coli (EHEC). Bacterial growth and Stx2 production were both inhibited by 2 mM NCT. The cytotoxic effect of Stx2 on Vero cells was removed by ≥5.5 mM NCT. Confocal microscopy and FACS analyses showed that the binding of S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
(81 reference statements)
0
15
0
Order By: Relevance
“…Measurements of the rate of consumption (decrease in oxidation capacity) confirmed this assumption (Eitzinger et al . ; Gottardi and Nagl ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Measurements of the rate of consumption (decrease in oxidation capacity) confirmed this assumption (Eitzinger et al . ; Gottardi and Nagl ).…”
Section: Discussionmentioning
confidence: 97%
“…Experiments to quantify this effect on a chemical basis, which included also bromine compounds, revealed the latter to be more reactive than their chlorine analogues. Under identical conditions (pH 7, 0Á005 mol l À1 active halogen in the presence of 0Á05% peptone), HOBr and the N-bromine derivatives of isocyanuric acid, and dimethylhydantoine lost 78-80% of the initial oxidation capacity within 1 h, while it was only 54-67% with the analogue N-chlorine compounds (Gottardi 1976). A further study using peptone and foetal calf serum revealed a throughout higher, but very similar consumption behaviour of the active bromine compounds compared to their chlorine analogues .…”
mentioning
confidence: 99%
“…Adherence of bacteria to surfaces is mediated by proteins in S. aureus (16), S. epidermidis (2), and P. aeruginosa (17). Since NCT and analog substances recently have been shown to directly inactivate bacterial toxins (8,18), it seems likely that the detachment of biofilms by NCT is due to an impact on these adherence proteins via oxidation of thiols and aromatic and amino groups (4,5). To clarify the exact molecular sites of attack could be an interesting item in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, secretory aspartyl proteinases of Candida albicans were downregulated by sublethal concentrations of NCT, and gliotoxin of Aspergillus fumigatus was obviously destroyed by this compound (56,57). Most recently, oxidation and chlorination of Shiga toxin of enterohemorrhagic Escherichia coli by NCT at multiple sites were demonstrated, leading to destruction and inactivation of the toxin (58).…”
Section: Nonmicrobicidal Effects Caused By Chloramine Compoundsmentioning
confidence: 99%